STRATEGIC THINKING AND BRANDS MOVE TO THE DIGITAL TRANSFORMATION - Daradkeh, Yousef Ibrahim; Gouveia, Luis Borges; Sen, Selin (MATTER: International Journal of Science and Technology, 2018)
For many, Digital Transformation can be considered the rethinking and exploration of technology, combined with business models, and processes that enable to add value for customers and employees and more effectively compete in an ever-changing digital economy.This paper discusses Digital Transformation and its exploration to provide a strategic orientation to organizations and their brands. Along the key factor for digital conversion, it's presented a SWOT analysis approach and a strategic thinking orientation to explore Digital Transformation in order to get stronger brands.The paper presents also some evidence from real world cases where such approach has been already used of considering a strategic approach to enable the Digital Transformation of brands.